Physical and Sensory Evaluation of Muffin Incorporated with Rubber Seed (Hevea brasiliensis) Flour, Pumpkin (Cucurbita moschata) Flour and Cassava (Manihot esculenta crantz) Flour - Noroul Asyikeen, Zulkifli; Hoon, Ho Lee; Nor Hidayah, Abu Hassan (2019)
This study was conducted to evaluate the physicochemical and organoleptic properties of muffin incorporated with different type of composite flour. In this study, three composites flour were produce with ratio 50:50 which are rubber seed and cassava flour (RCF), rubber seed and pumpkin flour (RPF) and cassava and pumpkin flour (CPF) and 100% wheat flour was used as control, to study their effect towards structural properties of muffin. The physicochemical and organoleptic properties (moisture, volume, texture, water activity, colour, pore size and sensory acceptance) of control and supplemented muffins were assessed. From the analysis, RPF showed the firmest texture 2.04±0.33 while RCF have high springiness 51.14±2.51 among the composite flour formulation. The addition of rubber seed flour in the formulation helps to improve the cell number of muffin which is 70 and 83 for RCF and RPF respectively. The RCF and CPF show lower moisture content than control which are 25.76±1.14 and 26.25±1.80 respectively. In terms of consumer acceptance, the RCF have the highest overall acceptability among tested composite flour. The incorporation of rubber seed flour into the RCF formulation improves the physical and organoleptic properties of the muffin.